Crossbred cows and food security in Ethiopia - Tangka, F.K.L. (University of Florida, 2001)
This study examines the food security and marketed surplus effects of intensified dairying in the peri-urban area of Addis Ababa, Ethiopia, where a market-oriented dairy production (MODP) system has been introduced for smallholders. Implications for policy formulation are drawn to help enhance the benefits of the new agricultural technologies. The data for the study are from 1999 primary data for 56 smallholder households. The ouseholds included two groups of 27 with crossbred cows and 29 without. Detailed household-level data were collected weekly (income, production, expenditures), monthly (food intake) and annually (demographics, resource endowments). The contrast between households using improved crossbred cattle and those using traditional cattle provides the basis for determining the extent to which the two sets of households allocate their resources differently and how their allocation decisions affect food security.